Konsep Pluralisme Agama Farid Esack - Soleh, A. Khudori (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
Farid Esack is one of the Islamic scholars concerning on religious pluralism. Pluralism, according to him, does not only deal with inclusiveness as Nur Kholis Madjid and Alwi Shihab thought and political interest-based as John Hick and Hans Kung concerned but also theological perspective. It means that the truth of other religions is not based on their only existence but because of Qur'anic acceptance textually to their existence beside Islam. According to Esack, al-Qur'an has clearly accepted other religions' existence beside Islam.